Eulogy [videorecording (DVD)] - Clancy, Michael; Clancy, Michael; Azaria, Hank, 1964-; Bradford, Jesse; Deschanel, Zooey, 1980- (Lions Gate Home Entertainment, 2004)
Three generations of a dysfunctional family gather to bury the family patriach. In the days leading up to the funeral, family secrets are revealed, old grudges resurface, and the household erupts with renewed vigor.